Evaluation of English-Language Learning Video on Food and Beverage Service using the CIPP Model: Evaluasi Video Pembelajaran Berbahasa Inggris Pelajaran Food and Beverage Service dengan Model CIPP - Salimatun, Salimatun; Sutadji, Eddy (Politeknik Assalaam Surakarta, 2025)
This study aims to evaluate and develop an English-language learning video for the Food and Beverage Service subject using the Research and Development (R&D) approach and the CIPP evaluation model (Context, Input, Process, Product). The learning video was developed to improve students' understanding of concepts in the hospitality field, specifically in the context of food and beverage service, as well as to enhance their English language proficiency. Data were collected through questionnaires, interviews, and direct observation during the learning process with the video. The evaluation results show that the learning video is effective in meeting the needs of students and instructors, increasing student engagement in the learning process, and improving students' understanding of English terms used in the hospitality field. Although there were some technical issues, such as device compatibility problems, overall, this video proved effective in improving students' English language skills in the context of food and beverage service. This study recommends further development of the learning video by addressing the technical issues and adding more varied content to improve the effectiveness of learning in the future.